Exploring Online Evaluation Development : A Bibliometric Approach - Sunarto, M.J. Dewiyani; Hariadi, Bambang; Koentjoro, Edo Yonatan; Effendi, Pradita Maulidya; Lemantara, Julianto; Soetomo, Erwin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to explore the growth of online evaluation to give a comprehensive overview and identify research in the trending field and recommendations for further research that can be developed. This study used a bibliometric approach with descriptive methods from documents in the last ten years of the Scopus database. Quantitative and qualitative analyses were performed using data collected from numerous scientific reference sources to determine development trends, the most popular subjects, and the contributions of eminent scholars. The analysis’s findings indicated that student evaluations of courses and teachers were the most commonly discussed subjects. However, in subsequent years, interest had changed to e-learning, higher education, assessment, and evaluation. Recent scientific articles further emphasized the significant impact Covid-19 had had on altering the evaluation process, placing particular attention on online learning. With the advancement of research on artificial intelligence in education, this study also outlined prospects and challenges in online evaluation research. We found thirteen publications covering Chat GPT for educational purposes by obtaining data from articles published in the most recent year in the Scopus database. This study offered a comprehensive view of the evolution of online evaluation through a bibliometric method, covered pertinent topics, and provided a basis for academics to carry out the most recent research in this area.